Measurement invariance of the Eating Disorder Examination in black and white children and adolescents. Issue 7 (3rd April 2017) - Burke, Natasha L.; Tanofsky‐Kraff, Marian; Crosby, Ross; Mehari, Rim D.; Marwitz, Shannon E.; Broadney, Miranda M.; Shomaker, Lauren B.; Kelly, Nichole R.; Schvey, Natasha A.; Cassidy, Omni; Yanovski, Susan Z.; Yanovski, Jack A.
Abstract: Objective: The Eating Disorder Examination (EDE) was originally developed and validated in primarily white female samples. Since data indicate that eating pathology impacts black youth, elucidating the psychometric appropriateness of the EDE for black youth is crucial. Methods: A convenience sample was assembled from seven pediatric obesity studies. The EDE was administered to all youth. Confirmatory factor analyses (CFA) were conducted to examine the original four‐factor model fit and two alternative factor structures for black and white youth. With acceptable fit, multiple‐group CFAs were conducted. For measurement invariant structures, the interactive effects of race with sex, BMI z, adiposity, and age were explored (all significance levels p  < .05). Results: For both black and white youth ( N  = 820; 41% black; 37% male; 6–18 years; BMI z −3.11 to 3.40), the original four‐factor EDE structure and alternative eight‐item one‐factor structure had mixed fit via CFA. However, a seven‐item, three‐factor structure reflecting Dietary Restraint, Shape/Weight Overvaluation, and Body Dissatisfaction had good fit and held at the level of strict invariance. Girls reported higher factor scores than boys. BMI z and adiposity were positively associated with each subscale. Age was associated with Dietary Restraint and Body Dissatisfaction. The interactional effects between sex, BMI z, and age with race were not significant; however, the interaction between adiposity and race was significant. At higher adiposity, white youth reported greater pathology than black youth. Conclusion: An abbreviated seven‐item, three‐factor version of the EDE captures eating pathology equivalently across black and white youth. Full psychometric testing of the modified EDE factor structure in black youth is warranted.